Paths Between the Locker Room and the Library: An Analysis of Role Conflict among Student Athletes - Camp, Henry J.; Epps, Jim (My University, 1986)
This paper examines the background concerning the inrerest in student-athlete role contlict and then raises a number of issues focusing on the anaiysis of role conflict. Suggestions are then offered as examples of ways to further research role conflict. The article discussed master status as a social identity marker, and athletes may only master "student" or "athlete" since they spend so much time on both roles. A pilot study was conducted to compare athletes' academic and athletic performance, with significant variability amongst "good" athletes iin terms of GPA outcomes.
Keywords: identity; academic performance